Naïve CD8+ T-Cells Engage a Versatile Metabolic Program Upon Activation in Humans and Differ Energetically From Memory CD8+ T-Cells - Nicoli, Francesco; Papagno, Laura; Frere, Justin J.; Cabral-Piccin, Mariela Pires; Clave, Emmanuel; Gostick, Emma; Toubert, Antoine; Price, David A.; Caputo, Antonella; Appay, Victor (Frontiers in Immunology, 2018)
Background: Characterization of the intracellular biochemical processes that regulate the generation and maintenance of effector and memory CD8+ T-cells from naïve precursors is essential for our understanding of adaptive immune responses and the development of immunotherapies. However, the metabolic determinants of antigen-driven activation and differentiation remain poorly defined, especially in humans. Methods: We used a variety of different approaches, including gene expression profiling and measurements of nutrient flux, to characterize the basal and activation-induced energetic requirements of naïve and phenotypically-defined subsets of human memory CD8+ T-cells. Findings: Profound metabolic differences were apparent as a function of differentiation status, both at rest and in response to stimulation via the T cell receptor (TCR). Of particular note, resting naïve CD8+ T cells were largely quiescent, but rapidly upregulated diverse energetic pathways after ligation of surface-expressed TCRs. Moreover, autophagy and the mechanistic target of rapamycin (mTOR)-dependent glycolytic pathway were identified as critical mediators of antigen-driven priming in the naïve CD8+ T cell pool, the efficiency of which was dampened by the presence of neutral lipids and fatty acids. Interpretation: These observations provide a metabolic roadmap of the CD8+ T-cell compartment in humans and reveal potentially selective targets for novel immunotherapies.